1980
DOI: 10.1111/j.1755-3768.1980.tb06692.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Tranexamic Acid on Secondary Haemorrhage After Traumatic Hyphaema

Abstract: During the period from March 1978 to November 1979, 232 consecutive patients with traumatic hyphaema were allocated by admission-date to conservative treatment and to treatment with the antifibrinolytic drug tranexamic acid. Secondary haemorrhage occurred in only two of 102 tranexamic acid treated patients, while secondary haemorrhage occurred in 12 out of 130 conservatively treated patients. This difference was statistically significant. Some clinical aspects of the rebleeding cases are presented and briefly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
30
1

Year Published

1983
1983
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 12 publications
3
30
1
Order By: Relevance
“…A meta-analysis of these three studies showed no statistically significant effect of tranexamic acid (OR 1.65, 95% CI 0.91 to 2.99; Figure 4). In addition, Varnek 1980 reported mean VAs of 0.9 in both the tranexamic acid and control groups at day five after the trauma. VA was not reported by Welsh 1983.…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…A meta-analysis of these three studies showed no statistically significant effect of tranexamic acid (OR 1.65, 95% CI 0.91 to 2.99; Figure 4). In addition, Varnek 1980 reported mean VAs of 0.9 in both the tranexamic acid and control groups at day five after the trauma. VA was not reported by Welsh 1983.…”
Section: Resultsmentioning
confidence: 94%
“…Five studies investigated the use of oral tranexamic acid compared with a control in treating traumatic hyphema (Rahmani 1999; Sukumaran 1988; Vangsted 1983; Varnek 1980; Welsh 1983). There were 581 participants included in the studies; 279 were assigned to tranexamic acid and 302 to a control intervention.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations